From green tide disaster to green resource: a multidisciplinary review of research progress and future prospects on Ulva prolifera - Zhongwei Chen; Zhongzhen Chen; Chengjuan Cao; Binbin Wang; Haibo Feng; Yuehao Ge; Bo Yang (Frontiers in Marine Science, 2026)
Ulva prolifera is the primary causative species of large-scale green tides in the Yellow Sea, posing recurrent threats to marine ecosystems and coastal economies. In recent years, research has undergone a fundamental shift from disaster control toward resource utilization. This multidisciplinary review synthesizes progress across the entire chain of green tide management, focusing on advances in monitoring and prediction. These include multi-source satellite remote sensing with deep learning, coupled hydrodynamic-ecological models for bloom forecasting, and eDNA-based early detection of micropropagules, alongside insights into ecological and physiological mechanisms such as allelopathic competition, nutrient-driven rapid growth, and stress adaptation traits that underpin bloom dominance. Besides, we also highlight breakthroughs in germplasm and cultivation, notably natural protoplast-based clonal propagation and the potential for genetic improvement using synthetic biology, alongside high-value resource utilization through the extraction of bioactive polysaccharides, the discovery of a thermostable ulvan lyase for efficient enzymatic processing, and the exploration of biomass for functional foods, pharmaceuticals, bioenergy, and biomaterials. This review further examines microbial degradation, including active microbial community succession and key degraders that transform organic matter and influence carbon cycling, and concludes with industrialization prospects centered on a closed-loop “early warning–precise interception –high-value conversion” framework. Unlike previous reviews that focused on individual aspects, this work explicitly linked ecological drivers to biotechnological applications and industrial feasibility. We critically examined how these domains connected, identified knowledge gaps, and proposed a roadmap for establishing U. prolifera as a model species for the marine bioeconomy. This integrated perspective transforms an environmental threat into a sustainable green resource.